Strategi Penyuluhan KB di Masa Pandemi Covid-19 - Dwi R, Nurwendah (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
At the moment, family planning counseling has become more challenging, along with the increasing complexity of the existing problems. Besides the population growth rate and technical issues, it also lacks personnel of counselors of family planning (PKB) ASN because many of them take their retirement. The KB officers have a duty in implementing activities of counseling, service, mobilization, and development of The Development Programs of Family Demography and Family Planning. To improve the success of family planning programs in the future, there is a need for coaching and development of Family Planning cadres that working in the IMP (Institute of Rural Communities), which consists of PPKBD, Sub PPKBD, and Family Planning group. In the Pandemic Covid-19, the counselor of KB and cadres of the IMP has experienced problems due to face to face meetings with the community and are also limited, and if forced to run a meeting should meet the protocol health. The KB officers need to run the mobilization strategy of the community through the 3P (organizing, strengthening, and mobilization) to the cadres of IMP. Several strategies that can be applied in coaching and counseling of family planning in the pandemic Covid-19 includes KIE/ Counseling/ Promotion of family planning through Media Communication and Network, make WhatsApp Group of Cadres, making the media KIE-based TI, video of short duration, and a flyer that can be delivered to the community through social media. Besides, it is also to introduce to some of the applications associated with the program Bangga Kencana that is the SKATA of BKKBN and Si LILI Keren (Information System for Field Line Workers and IMP cadres. It is hoped that in the future, with the Bangga Kencana program, all Indonesian families will become happy, prosperous, independent, and high-quality families